Faktor-faktor Kejayaan dalam Pelaksanaan MS 1900:2005: Satu Kajian Kualitatif di Institusi Pengajian Tinggi Swasta, Malaysia (Sains Humanika, 2015)
MS 1900 is a standard of Quality Management Systems–Requirements From Islamic Perspective actually was introduced in Malaysia since 2005. The introduction of this system among others, to ensure implementation of the organization management meets the Islamic teaching and not involved in negative elements that forbidden by Shari’ah. The system was developed using the ISO 9001 standard as a basic for the effectiveness of the products or services to satisfy customers. QMS MS 1900 standard that differs from the others because there is infusion of Shari’ah compliance as an additional element. Therefore, this study aims to identify the factors that contribute to the successful of MS 1900’s implementation in private higher education institution (HEI) in Malaysia. The methodology used qualitative design with the case study method by using semi-structured interviews which were recorded, transcribed and analyzed about the implementation of that quality system. Besides that, observation and documents review were also employed as data collection method. The interviewees consisted of various groups of employees who working in this institution and directly involved in the implementation of MS 1900. The findings found that majority of the interviewees in this private HEI explains there are six critical success factors in the implementation of MS 1900 which affect their job satisfaction, namely reward systems, communication, employee participation, leadership commitment, organization culture, and last factor is the leadership style. Thus, the implications for this system implementation, the limitations and several other recommendations were also presented as a guideline for improvement in the implementation of QMS from the Islamic perspective.
Keywords: Quality management system from Islamic perspective (MS 1900); employee satisfaction; critical success factors of QMS